Workshop Penulisan Ilmiah Menggunakan Teknologi AI Dan Ethical Standart Bagi Siswa SMAN 5 Makassar - Ibrahim, Zulfadli; Ashabul Kahfi Susanto; Dewi Triantini; Muhammad Ihsan Zulfikar; Mentari S. Sitorus (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2025)
Scientific writing is a crucial skill for high school students to support critical thinking and academic literacy. To address this, a workshop was conducted at SMA Negeri 5 Makassar to enhance students’ scientific writing skills and introduce ethical AI usage. The activity was planned to begin with identifying the problems and needs of the partner school, followed by preparing workshop materials, conducting the workshop, and concluding with evaluation and follow-up actions. The program included interactive lectures, demonstrations of AI tools, and guided writing exercises focused on crafting titles, backgrounds, and literature reviews. Pre- and post-tests revealed significant improvement. Understanding of title writing increased from 40% to 87%, background structure from 30% to 80%, and literature review structure from 17% to 67%. Knowledge of AI tools rose from 70% to 100%, while comprehension of prompting techniques and AI’s role in writing both reached 100% after the workshop. Notably, awareness of ethical AI usage, initially absent among participants, reached 100%. Understanding of transparency in AI-assisted writing also increased dramatically from 3% to 100%. Overall, the workshop effectively improved both technical and ethical aspects of scientific writing, preparing students to face academic challenges with greater confidence and responsibility.